Limited geographic genetic structure detected in a widespread Palearctic corvid, Nucifraga caryocatactes - Dohms, Kimberly M.; Burg, Theresa M. (PeerJ, 2014)
The Eurasian or spotted nutcracker (Nucifraga caryocatactes) is a widespread resident corvid found throughout the Palearctic from Central Europe to Japan. Characterized by periodic bouts of irruptive dispersal in search of Pinus seed crops, this species has potential for high levels of gene flow across its range. Previous analysis of 11 individuals did not find significant range-wide population genetic structure. We investigated population structure using 924 base pairs of mitochondrial DNA control region sequence data from 62 individuals from 12 populations distributed throughout the nutcracker’s range. We complemented this analysis by incorporating additional genetic data from previously published sequences. High levels of genetic diversity and limited population genetic structure were detected suggesting that potential barriers to dispersal do not restrict gene flow in nutcrackers.
Keywords: Nucifraga caryocatactes; Eurasian nutcracker; Phylogeography; Palearctic distribution; Corvid; Mitochondrial DNA